2013
DOI: 10.4028/www.scientific.net/msf.747-748.844
|View full text |Cite
|
Sign up to set email alerts
|

β Grain Growth Kinetics of a New Metastable β Titanium Alloy

Abstract: Ti-Mo-Nb-Cr-Al-Fe-Si alloy is a new metastable β titanium alloy with excellent combination of strength and ductility. The β grain-growth exponent and the activation energies for β grain growth for the investigated alloy at specified temperature were computed by the kinetic equations and the Arrhenius-type equation. The rate of β grain growth decreases with elongating solution treated time and increases with the increasing solution-treated temperature. The β grain-growth exponents, n, are 0.461, 0.464 and 0.469… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In previous research, it has been reported that the activation energy for grain boundary self-diffusion in β titanium alloys ranged from 145−315 kJ mol −1 [28]. The grain-growth activation energy for TC4-DT alloy that obtained from the modified model exists in the lower portion within this range, which is higher than 20 kJ mol −1 for pure Ti and 56 kJ mol −1 for Ti-0.2Pd alloy, and smaller than that of other titanium alloys with high solute element, such as 274 kJ mol −1 for Ti-Mo-Nb-Cr-Al-Fe-Si alloy [29] and 272.16 kJ mol −1 for Ti-20Mo alloy [30]. The content of solute atoms has a significant effect on the activation energy of graingrowth, which results from the fact that a high solute addition can retard the grain-boundary migration, leading to the high activation energy and different growth kinetics.…”
Section: 741mentioning
confidence: 82%
“…In previous research, it has been reported that the activation energy for grain boundary self-diffusion in β titanium alloys ranged from 145−315 kJ mol −1 [28]. The grain-growth activation energy for TC4-DT alloy that obtained from the modified model exists in the lower portion within this range, which is higher than 20 kJ mol −1 for pure Ti and 56 kJ mol −1 for Ti-0.2Pd alloy, and smaller than that of other titanium alloys with high solute element, such as 274 kJ mol −1 for Ti-Mo-Nb-Cr-Al-Fe-Si alloy [29] and 272.16 kJ mol −1 for Ti-20Mo alloy [30]. The content of solute atoms has a significant effect on the activation energy of graingrowth, which results from the fact that a high solute addition can retard the grain-boundary migration, leading to the high activation energy and different growth kinetics.…”
Section: 741mentioning
confidence: 82%
“…In addition, most of the metastable β titanium alloys contain alloy elements which could improve the strength of α phase through solution strengthening. Therefore, the metastable β titanium alloy can obtain higher strength level than α+β phase titanium alloy [17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…Eventually, the uniform and refined b grains are formed. However, the recrystallization kinetics of b grains in the b region is extremely fast [28,29]. Therefore, the refining of b grains is not very effective.…”
Section: Microstructure and Recrystallizationmentioning
confidence: 99%